A Content Analysis for Interconnection between Language and Social Etiquettes (Architecture Image Studies, 2025)
This paper explores the intricate relationship between language and social etiquette, emphasizing how linguistic choices reflect and shape social norms across diverse cultural contexts while having content analysis. Using a qualitative meta-analysis, this study synthesizes findings from existing research to identify recurring content catagories, such as the use of politeness strategies, language as a marker of social identity, and cultural variations in language etiquette. Findings reveal that politeness strategies, like formal address and indirect communication, serve as tools for maintaining social harmony, while language functions as a marker of identity, allowing individuals to align with social groups. Additionally, cultural differences significantly influence etiquette, with hierarchical societies often preferring more deferential forms of communication. This analysis underscores the vital role language plays in mirroring and reinforcing societal values, calling for continued research on how evolving language practices impact social behavior and etiquette.